Manufacturing Simulation with Plant Simulation and SimTalk Usage and Programming with Examples and Solutions - Bangsow, Steffen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book provides the first comprehensive introduction to Plant Simulation. It supports new users of the software to get started quickly, provides an excellent introduction how to work with the embedded programming language SimTalk and even helps advanced users with examples of typical modeling tasks. The book focuses on the basic knowledge required to execute simulation projects with Plant Simulation which is an excellent starting point for real life projects.
Introducing Factory Simulation -- Plant Simulation -- Standard Classes in PLANT SIMULATION -- Icons -- Programming with SimTalk -- Simtalk and Material Flow Objects -- Mobile Units -- Information Flow Objects -- Statistics -- User Interface Objects -- Data Exchange -- Plant Simulation 3D.
Keywords: Engineering; Computer simulation; Computer aided design; Industrial engineering; Business logistics; Engineering; Industrial and Production Engineering; Production/Logistics.; Computer-Aided Engineering (CAD, CAE) and Design; Operations Research/Decision Theory; Simulation and Modeling